Strain Energy Harvesting Powered Wireless Sensor Node for Aircraft Structural Health Monitoring. (2016) - Chew, Zheng Jun; Ruan, Tingwen; Zhu, Meiling
Abstract: This paper presents a wireless sensor node (WSN) powered by a strain energy harvester (SEH) through an adaptive power management module (PMM) for aircraft structural health monitoring (SHM). The energy distribution in the system, the efficiencies of the whole systems, and the WSN powering capability of the SEH under different strain loadings were studied to understand the developed system performance for practical applications of an autonomous WSN. Experimental results show that the SEH is able to produce up to 3.34 mW under strain loading of 600 μɛ at 10 Hz. The WSN can be powered up through the adaptive PMM at efficiency from 70 to 80% under different test conditions.